Examining Emphysematous Pyelonephritis: A Case Study on Diagnosis and Outcomes - Mahnoor Mahnoor; Syeda Aina Ali; Saira Nasir; Moiz Azmat; Hafiz Muhammad Umer Farooqi (Emergency Care and Medicine)
Background: Emphysematous pyelonephritis (EPN) is an infectious disease of the renal system caused by gas-producing microorganisms harboring the kidneys. Patients with diabetes mellitus (DM), an endocrine disease with hyperglycemia, are particularly susceptible to the EPN as their immune system is compromised in fighting against infections. Case Description: We present a case of a 50-year-old female with a history of chronic diabetes and persistent hypertension. She presented with symptoms of pyrexia and flank pain. Following findings from ultrasound, she was advised to undergo computed tomographic (CT) scans that reveal air-filled hypodense areas at the upper and mid pole of the right kidney and in the renal pelvis of the right ureter, which confirms the class I EPN in the patient. Urine culture identifies Escherica coli as the causative agent for EPN. The patient was managed with third-generation antibiotics over two weeks, leading to full recovery without surgical intervention. Discussion: The availability of CT imaging makes early diagnosis and reduces mortality associated with EPN. Conservative medical management should be the initial treatment strategy for EPN. However, severe cases require immediate therapeutic action. In our case, the patient was treated with antibiotic therapy and recovered. Conclusions: CT scan seems to be the optimal diagnosis in patients with acute emphysematous pyelonephritis. Patients with EPN class I respond well to medical treatment with excellent outcomes.